Differences in Graduation and Persistence Rates over Time for African-American Students at Texas 4-Year Universities - Jerrell Sherman; John R. Slate (Athens Institute for Education and Research, 2020)
In this study, the graduation and persistence rates of African-American students at Texas 4-year universities were examined for the 2003-2004 academic year, the 2009-2010 academic year, and the 2014-2015 academic year. Of specific interest was whether the graduation and persistence rates for African-American students changed over an 11-year time period in Texas, from 2003-2004 to 2014-2015. Inferential statistical analyses did not reveal the presence of any statistically significant differences in the 1-year graduation and persistence rates of African-American students over the 11-year time period that were investigated. The 1-year graduation and persistence rates were stable, ranging only from 53% to 56%, over this 11-year time period. Suggestions for policy and for practice, as well as recommendations for future research, were mentioned.